ASSESSMENT AND UTILIZATION OF DRUG INFORMATION SERVICES AND CREATING AWARENESS FOR ENHANCED UTILIZATION OF DRUG INFORMATION CENTRE IN A TERTIARY CARE TEACHING HOSPITAL - Peter, Ann Varsha; Murali, Anusha; Tomy, Tilu; Londhe, Sushilkumar P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To assess the utilization of drug information services and create awareness for enhanced utilization of drug information centre in the hospital. Methodology: A retro-prospective observational study conducted from September 2015 to February 2016. The data obtained from DI request, documentation and feedback forms are analyzed for the parameters such as professional status of enquirer, mode of receipt of query, purpose of enquiry, time frame to reply and references used. Awareness about drug information services was created in the hospital by circulating brochures and interacting with healthcare professionals. Result: A total of 943 queries were retrospectively analysed. Most of the queries obtained from PG/intern (50.27%), during ward rounds (57.48%) and asked for updating knowledge (76.35%). Frequently asked questions were about indications of drugs (18.60%). Mostly answers given as printed (66.70%), replied within a day (46.45%) by using Micromedex (54.72%). Majority of the enquirers rated the DI services as good (54.93%). A total of 394 queries were prospectively analysed. Most of the queries obtained from physicians (42.23%), during ward rounds (59.89%) and asked for updating knowledge (49.49%). Frequently asked questions were about ADRs (21.28%). The mode of reply for the queries given mostly in printed format (41.14%), replied within 2-4hrs (33.75%) by using Micromedex (40.56%). Majority of the enquirers rated the DI services as good (46.98%). Conclusion: The drug information services provided were useful to various healthcare professionals to maintain rational drug therapy by giving unbiased and well-reviewed information. Â Â 